Impact of a College Freshman Social and Emotional Learning Curriculum on Student Learning Outcomes: An Exploratory Study - Wang, Ning; Wilhite, Stephen; Wyatt, Jeannette; Young, Thomas; Bloemker, Geraldine; Wilhite, Emily (Journal of University Teaching and Learning Practice, 2012)
This study investigates the impact of implementing a social and emotional learning curriculum for college freshmen on student learning outcomes, including social and emotional competence and academic performance. Through the use of a quasi-experimental design, the growth in social and emotional competence of students who participated in the social and emotional learning seminars is compared with that of students who were enrolled in other freshman seminars. This comparison is complemented by a qualitative analysis of students’ self-reflections in relation to specific dimensions of social and emotional competence. The results of this study suggest that exposure to a social and emotional learning curriculum during the first semester at college may contribute to the development of social and emotional competence in students. Because of the potential relationship of social and emotional competence to academic success, this study also reports a comparison of the grade point averages (GPAs) of students from the social and emotional seminars with the GPAs of students from the other freshman seminars, while controlling for other predictors of academic success. The results indicate that students exposed to the social and emotional learning curriculum had higher grades than other students across the four semesters following the completion of the seminar.